Pengaruh Pembakaran Beton Yang Direndam dalam Larutan Asam, Basa, Dan Garam Terhadap Kekuatan Beton - Stephen Gray; Herman Parung; Olan Jujun Sanggaria (Program Studi Teknik Sipil UKI Paulus-Makassar, 2023)
This study explains the use of solution variations in the concrete soaking process, knowing the increase in concrete soaked in variations of concrete soaking solutions. As well as knowing the decrease in the strength of concrete due to combustion at high temperatures. This study aims to determine the improvement of concrete quality in the form of mechanical properties, namely compressive strength, split tensile strength, and bending strength. The collection of aggregate material was carried out in Pucak River, Maros Regency, South Sulawesi. The variations of the immersion solution used are Seawater, Hydrochloric acid (HCL), Sodium Hydroxide (NaOh). While the variation in the duration of burning concrete is 0 hours and 3 hours. This study showed that the results of concrete compressive strength in soaking variations experienced the highest percentage increase in normal water immersion, namely 17.728% while the lowest occurred in hydrochloric acid soaking of 0.652%. Then after 3 hours of combustion with a temperature of 3650 C the highest percentage decrease occurred in the immersion of hydrochloric acid by 27.678%. Test results decreased tensile strength the highest split in hydrochloric acid immersion by 38.824%, 3, the lowest in normal water immersion by 30.275%. The results of the Bending Strength Test experienced the highest decrease in hydrochloric acid immersion by 26.316%, the lowest in normal water immersion by 21.154%. The use of solution variations in concrete soaking still meets the compressive strength of the plan whereas in burning concrete for 3 hours resulting in a decrease in the strength of the concrete which indicates the concrete is not viable in function.